2013
DOI: 10.1038/cddis.2013.371
|View full text |Cite
|
Sign up to set email alerts
|

Cornelia de Lange Syndrome: NIPBL haploinsufficiency downregulates canonical Wnt pathway in zebrafish embryos and patients fibroblasts

Abstract: Cornelia de Lange Syndrome is a severe genetic disorder characterized by malformations affecting multiple systems, with a common feature of severe mental retardation. Genetic variants within four genes (NIPBL (Nipped-B-like), SMC1A, SMC3, and HDAC8) are believed to be responsible for the majority of cases; all these genes encode proteins that are part of the ‘cohesin complex'. Cohesins exhibit two temporally separated major roles in cells: one controlling the cell cycle and the other involved in regulating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
68
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 60 publications
11
68
0
1
Order By: Relevance
“…We have previously reported comparable abnormalities in models for NIPBL (Pistocchi et al, ). Hence, we decided to explore the genetic interactions of these two cohesins that when mutated produce similar but distinct phenotypes in humans.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…We have previously reported comparable abnormalities in models for NIPBL (Pistocchi et al, ). Hence, we decided to explore the genetic interactions of these two cohesins that when mutated produce similar but distinct phenotypes in humans.…”
Section: Resultssupporting
confidence: 72%
“…Monnich et al () described the expression and preliminary functional studies of the smc1al paralog, showing that this gene encodes for a cohesin subunit and its knock‐down leads to cell cycle arrest (Dickinson and Horsfield, unpublished data). Moreover, the smc1al mutant generated in an insertional mutant screening (Amsterdam et al, ) resembles the phenotype of other mutants for cohesin genes such as rad21 and smc3 , and consistent with models of nipbl ‐haploinsufficiency (Muto et al, ; Pistocchi et al, ). We have investigated the expression and function of the paralog smc1a .…”
Section: Resultssupporting
confidence: 60%
“…Wnt3a signaling was previously shown to induce enhancer-promoter looping at the c-MYC gene in cancer cells (Yochum et al, 2010), and consistent with this, β-catenin transactivation was found to require cohesin during zebrafish development (Pistocchi et al, 2013). Consequently, we asked whether β-catenin similarly directs formation of enhancer loops at ME genes.…”
Section: Resultssupporting
confidence: 59%
“…Based on earlier observations that β-catenin:LEF-1 complexes upregulate c-Myc expression in cancer cells through enhancer-promoter looping (Yochum et al, 2010), and that cohesin is required for Wnt: β-catenin transactivation in zebrafish development (Pistocchi et al, 2013), we asked whether Wnt3a signaling also facilitates looping at ME genes. Chromatin conformation capture (3C) and ChIP-seq experiments revealed that Wnt3a induces binding of cohesin to LEF-1 enhancers, and increased physical enhancer-promoter contacts at the two ME genes we tested, MIXL1 and EOMES .…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish is a powerful and penetrant model in which to study human disease, including cohesinopathies (Horsfield et al, ). For instance, the Zebrafish CNS, heart, gut, cephalic structures, and skeleton appear exquisitely sensitive to cohesins, Nipbl, and Esco2 levels (Muto et al, ; Pistocchi et al, ; Muto et al, ; Banerji et al, ; Fazio et al, ). Similar to that of humans, the Zebrafish genome harbors orthologues of most cohesion genes ( nipbla and nipblb; esco1 and esco2; smc1a and smc1al; smc3; rad21a and rad21b; stag1a/b and stag2a/b and stag3 ; pds5a and pds5b ).…”
Section: Part I: Area Of Study and Significancementioning
confidence: 99%